Novel Functional Properties of Missense Mutations in the Glycine Receptor β Subunit in Startle Disease - Piro, Inken; Eckes, Anna-Lena; Kasaragod, Vikram Babu; Sommer, Claudia; Harvey, Robert J.; Schaefer, Natascha; Villmann, Carmen (Frontiers in Molecular Neuroscience, 2021)
Startle disease is a rare disorder associated with mutations in GLRA1 and GLRB, encoding glycine receptor (GlyR) α1 and β subunits, which enable fast synaptic inhibitory transmission in the spinal cord and brainstem. The GlyR β subunit is important for synaptic localization via interactions with gephyrin and contributes to agonist binding and ion channel conductance. Here, we have studied three GLRB missense mutations, Y252S, S321F, and A455P, identified in startle disease patients. For Y252S in M1 a disrupted stacking interaction with surrounding aromatic residues in M3 and M4 is suggested which is accompanied by an increased EC50 value. By contrast, S321F in M3 might stabilize stacking interactions with aromatic residues in M1 and M4. No significant differences in glycine potency or efficacy were observed for S321F. The A455P variant was not predicted to impact on subunit folding but surprisingly displayed increased maximal currents which were not accompanied by enhanced surface expression, suggesting that A455P is a gain-of-function mutation. All three GlyR β variants are trafficked effectively with the α1 subunit through intracellular compartments and inserted into the cellular membrane. In vivo, the GlyR β subunit is transported together with α1 and the scaffolding protein gephyrin to synaptic sites. The interaction of these proteins was studied using eGFP-gephyrin, forming cytosolic aggregates in non-neuronal cells. eGFP-gephyrin and β subunit co-expression resulted in the recruitment of both wild-type and mutant GlyR β subunits to gephyrin aggregates. However, a significantly lower number of GlyR β aggregates was observed for Y252S, while for mutants S321F and A455P, the area and the perimeter of GlyR β subunit aggregates was increased in comparison to wild-type β. Transfection of hippocampal neurons confirmed differences in GlyR-gephyrin clustering with Y252S and A455P, leading to a significant reduction in GlyR β-positive synapses. Although none of the mutations studied is directly located within the gephyrin-binding motif in the GlyR β M3-M4 loop, we suggest that structural changes within the GlyR β subunit result in differences in GlyR β-gephyrin interactions. Hence, we conclude that loss- or gain-of-function, or alterations in synaptic GlyR clustering may underlie disease pathology in startle disease patients carrying GLRB mutations.